The autoantibody rheumatoid factor may be an independent risk factor for ischaemic heart disease in men. Issue 10 (5th June 2007) - Edwards, C J; Syddall, H; Goswami, R; Goswami, P; Dennison, E M; Arden, N K; Cooper, C; ,
Abstract : Background: Subjects with rheumatoid arthritis have an increased prevalence of ischaemic heart disease (IHD). This is most likely in those people with the autoantibody rheumatoid factor (RF). RF is strongly associated with rheumatoid arthritis (RA) but is also present in up to 15% of all adults. Objective: To determine whether RF might identify people in a general population who also share an increased likelihood of developing IHD. Methods: Subjects from the Hertfordshire Cohort Study were investigated for the presence of RF. Subjects completed a questionnaire and attended a clinic where a history of IHD was recorded (ECG, coronary artery bypass grafting, Rose chest pain). Associations between the presence of RF, antinuclear antibodies (ANA), anticardiolipin antibodies (ACA) and IHD in 567 men and 589 women were investigated and compared with traditional risk factors for IHD. Results: RF was associated with an increased likelihood of IHD in men (odds ratio (OR) = 3.1, 95% CI 1.7 to 5.4, p<0.001). This increased risk could not be explained by traditional risk factors for IHD (mutually adjusted OR for RF 2.9 (95% CI 1.6 to 5.3), p<0.001). There was no significant association between RF in women or between ANA or ACA with IHD in men or women. Conclusion: This work suggests that RF is an independent risk factor for IHD in the general population. It lends support to the importance of inflammation in atherosclerosis and suggests that autoimmune processes may be involved. In addition, it raises the intriguing possibility that RF may have a direct role in the pathogenesis of IHD in some subjects.